2013
DOI: 10.2217/pgs.13.32
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoblastoid Cell Lines in Pharmacogenomics: How Applicable are They to Clinical Outcomes?

Abstract: Opinion LCLs are widely used in pharmacogenomic studies and the applicability of LCLs for various clinical phenotypes is emerging. Early studies have yielded promising results for LCLs as a proxy for genetic variants for treatment outcome for a number of cancers as well as toxicity in varying tissue types including taxane-induced neuropathy. Although LCLs have demonstrated utility in the elucidation of functional mechanisms for results of clinical genotype-drug phenotype studies, there are more relevant cell-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For instance, we have previously shown that lymphoblastoid cells preserve their inter-individual variation in adhesion to endothelial cells, an important leukocyte property in retinopathy [ 9 ]. Lymphoblastoid cell lines have been shown to be relevant not only to white blood cells but also to a diverse array of different tissues [ 8 , 10 12 ]. Recent findings of the GTEx study confirm the substantial overlap in the genetic architecture for gene expression between lymphoblastoid cells and other tissues [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we have previously shown that lymphoblastoid cells preserve their inter-individual variation in adhesion to endothelial cells, an important leukocyte property in retinopathy [ 9 ]. Lymphoblastoid cell lines have been shown to be relevant not only to white blood cells but also to a diverse array of different tissues [ 8 , 10 12 ]. Recent findings of the GTEx study confirm the substantial overlap in the genetic architecture for gene expression between lymphoblastoid cells and other tissues [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies have identified loci for drug-related phenotypes in humans, mice and lympoblastoid cells. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 However, the yield of genetic loci has been low. In addition, successes have generally been limited to the idiosyncratic side effects of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can uncover previously unrecognized mechanisms of drug response and provides information on the associated biological pathways. Lymphoblastoid cell lines (LCLs) constitute a well-established pharmacogenomic model for genome-wide expression profiling [ 18 , 19 ]. Although there has been some debate about biological noise related to confounding factors, LCLs have been used to assess gene sets involved in responses to anticancer drugs such as bleomycin, gemcitabine, cytosine arabinoside, and 5-fluorouracil [ 20 - 24 ].…”
Section: Introductionmentioning
confidence: 99%